Monitoring of offshore platform deformation with stanford method of Persistent Scatterer (StaMPS) - Latip, A.S.A. (IEEE Computer Society, 2015)
Numerousstudies have proven that the Persistent Scatterer Interferometry (PSI) technique has been successfully utilized for land subsidence monitoring, slope stability monitoring, volcano deformation, earthquake deformation, urban deformation and dike monitoring. However, the ability of the PSI technique for the application of the offshore structures such as offshore oil platform has been less recognized. With the PSI technique, the deformation information can be extracted from man-made features of offshore structures which having high radar backscatter response. Therefore, this paper investigates the capabilities of PSI technique using Stanford Method of Persistent Scatterer (StaMPS) for monitoring deformation phenomena of an offshore platform. A total number of 11 highresolution X-band data from Terra SAR-X radar images covering the period from 2012 to 2013 are utilized to apply the StaMPS method. The results show deformation rate of the offshore platform is in the range between -6 mm/year and 8.1 mm/year and its standard deviation from 0.8 to 3.1 mm/year which is comparable to deformation monitoring result from Global Positioning System(GPS) technique done earlier. Therefore, it shows the potential of using the PSI technique for such deformation monitoring of offshore structures. Â© 2015 IEEE.